The Relationship Of Mother's Knowledge Level Towards Pregnancy Class With Exclusive Breastfeeding Success - Sehmawati; Rosmala Kurnia Dewi; Pintam Ayu Yastirin (LPPM AN NUUR, 2022)
Background: Pregnant women class is a study group for pregnant women with a maximum number of 10 participants. In this class, pregnant women will learn together, discuss and share experiences, about maternal and child health (MCH) thoroughly and systematically and can be carried out on a scheduled and continuous basis. Classes for pregnant women are facilitated by midwives/health workers using a class package for pregnant women, which consists of a MCH handbook, flip charts, guidelines for implementing classes for pregnant women, a guide for class facilitators for pregnant women, and exercise books for pregnant women (Kemenkes RI, 2014). Purpose: Knowing the relationship between the level of knowledge of mothers in attending classes for pregnant women with exclusive breastfeeding. Method: The type of research used is analytic with a cross section approach, the sample test used is saturated sampling, with the sample used is 30 breastfeeding mothers. The status test uses the Square test (Chi Square). Results: This research was conducted on 30 respondents with good knowledge of postpartum mothers about the success of breastfeeding, namely 25 people (83.3%), exclusive breastfeeding, namely 23 people (76.7%), value of 0.006 < 0 ,05. Conclusion: A good level of knowledge of postpartum mothers in taking classes for pregnant women on a regular basis will provide the success of breastfeeding mothers in providing exclusive breastfeeding.